The 1600 Collection of Madrigals By Thomas Weelkes - (:unkn) unknown (My University, 2014)
Thomas Weelkes in considered among the most important of the English madrigalists of the late sixteenth and early seventeenth centuries; however, little has been written about him. Modern scholarship begins with Edmund H. Fellowes's edition of Weelkes's madrigal publications. The only comprehensive study of Weelkes's life and works is David Brown's 1969 Thomas Weelkes: A Biographical and Critical Study. Most other Weelkes scholarship simply compares his music to that of his contemporaries. This thesis fills another gap in Weelkes studies by offering an analysis of his 1600 collection, Madrigals of 5 and 6 Parts, Apt for the Viols and Voices. The historical backdrop for the publication and success of the 1600 collection includes a brief overview of Weelkes's biography and network of patronage, as well as Alfonso Ferrabosco's introduction of the madrigal to England, and Nicholas Yonge's 1588 Musica transalpina. This is then followed by an analysis of the construction and unusual organization of the collection with discussions of the relevant theories of Weelkes scholars Fellowes, Brown, and Thurston Dart. Weelkes's establishment of a native madrigal style in England was accomplished by his employment of expressive compositional devices such as word painting and chromaticism. The thesis concludes with an examination of the legacy of Weelkes's 1600 collection of madrigals and the significant place it holds among the most important of the English madrigal collections.
Keywords: Chromaticism; English Madrigal; Madrigals of 5 and 6 Parts (1600); Music Publishing; Thomas Weelkes; Word Painting